LEVEL BERPIKIR KRITIS SISWA DALAM MENYELESAIKAN MASALAH OPEN ENDED MATEMATIKA - Hananto Purbonugroho; Teguh Wibowo; Heru Kurniawan (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2021)
This research was conducted with the aim to determine the level of critical thinking of students in solving open ended mathematics problem. This type of research is qualitative. The subjects of this study were 3 students of class VIII who had been chosen purposively is students with high mathematical abilities. Data Validity Test uses triangulation techniques. Data collection techniques using critical thinking test questions. The results showed that students with high mathematical abilities reached level 3 in critical thinking.